Turning right in the sixties : the conservative capture of the GOP - Brennan, Mary C. (University of North Carolina Press, 1995)
In Turning Right in the Sixties, Mary Brennan describes how conservative Americans from a variety of backgrounds, feeling disfranchised and ignored, joined forces to make their voices heard and by 1968 had gained enough power within the party to play the decisive role in determining who would be chosen as the presidential nominee. Building on Barry Goldwater's shortlived bid for the presidential nomination in 1960, Republican conservatives forged new coalitions, aided by an increasingly vocal conservative press, and began to organize at the grassroots level. Their goal was to nominate a conservative in the next election, and eventually they gained enough support to guarantee Goldwater the nomination in 1964. Liberal Republicans, as Brennan demonstrates, failed to stop this swing to the right. Brennan argues that Goldwater's loss to Lyndon Johnson in the general election has obscured the more significant fact that conservatives had wrestled control of the Republican Party from the moderates who had dominated it for years. The lessons conservatives learned in that campaign aided them in 1968 when they were able to force Richard Nixon to cast himself as a conservative candidate, says Brennan, and also laid the groundwork for Ronald Reagan's presidential victory in 1980.